DINAMIKA MAJLIS TA’LIM DI PEDESAAN TAHUN 1970-2010 - Ristiyanto, Sugeng (Kopertais Wilayah X Jawa Tengah, 2012)
AbstrakThe people living in Mlandang, one of the rural areas in Karanganyar, are muslims. However, they had not developed their religiosity and traditions well until 1980s when a non formal Islamic teaching called Sunday Afternoon Islamic Teaching was founded by Ismadi, an Elementary School teacher. Through this institution, muslims’ religiosity limited to prayers, fasting, charity, and reading Kuran has developed into wider and more intensive scale. Now, there are many muslims capable of reading Kuran and giving speech. Most of them perform regular prayers, pay regular and accidental charity, join local Islamic teaching, and live according to Islam. They also have better mosque, kindergarten, and other facilities. Local traditions, on the contrary, undergo changes in forms and intensity. The traditions close to Islamic teaching such as that related to birth are changed and continued. On the contrary, the ones far from Islamic origins such as those related to farming, marriage, and death are left. Key words: Dinamika, Majlis ta’lim, Keberagamaan, Tradisi